FEATURES OF ACCOUNTING IN CLUSTER FARMS IN THE CONTEXT OF DIGITALIZATION - Sativaldieva Gulchehra Khudaiberdievna (Scholar Express Journals, 2022)
The article reveals the need to create cluster farms. Importance of accounting information for cluster management. The procedure for their collection, provision, storage and use in the course of activities. The main attention is paid to the preparation of information for external and internal users in the context of digitalization, as well as the connection of the accounting information system with other information systems.
Keywords: cluster; digitalization; accounting; management accounting